2018
DOI: 10.1016/j.cgh.2017.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in the Treatment of Autoimmune Hepatitis

Abstract: Dear Editor:Corticosteroids and azathioprine (AZA) are standard initial treatment of autoimmune hepatitis (AIH) while up to 20% of patients do not respond, or are intolerant to this treatment. 1 In Clinical Gastroenterology and Hepatology, several reports have shown that mycophenolate mofetil, tacrolimus, 6-mercaptopurine, and 6thioguanine are effective and safe second-line therapies for AIH. 2-6 More recently, Haridy et al 7 reported efficacy and safety of methotrexate (MTX) as alternative therapy in 11 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has recently been suggested that a combination of these mechanisms may be the key to its full immunosuppressant efficacy [95]. A successful use of MTX in treatment of AIH has been repeatedly reported since the late 1990s [50,96,97]. However, all of these reports only described successful treatment of single patients, including two pediatric cases [98].…”
Section: Methotrexatementioning
confidence: 99%
“…It has recently been suggested that a combination of these mechanisms may be the key to its full immunosuppressant efficacy [95]. A successful use of MTX in treatment of AIH has been repeatedly reported since the late 1990s [50,96,97]. However, all of these reports only described successful treatment of single patients, including two pediatric cases [98].…”
Section: Methotrexatementioning
confidence: 99%